Tuning magnetic properties of non-collinear magnetization configuration in Pt/[Pt/Co](6)/Pt/Co/Pt multilayer structure - DEĞER, CANER (ELSEVIER SCIENCE BV, 2017)
In this study, effects of Pt spacer and Co reference layers thickness in [Co/Pt](6)/Pt/Co multilayer have been revealed to tailor magnetization directions in non-collinear configuration. Magneto-optic Kerr effect and ferromagnetic resonance techniques were employed to investigate magnetic properties. Bilinear coupling between [Co/Pt](6) and Co layers and anisotropy constants were determined by a micromagnetic simulation based on metropolis algorithm. 3 nm spacer causes ferromagnetic coupling while the samples have 4 and 5 nm spacer are coupled anti-ferromagneticaly. Also, tuning magnetic anisotropy of [Co/Pt](6) layer was accomplished by Co reference layer. It is revealed that controlling of non-collinear states in such systems is possible by variation of thickness of spacer and reference layers and [Co/Pt](6)/tPt/tCo trilayer system can be used in multilayered magnetic systems. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Non-collinear magnetic configuration; Interlayer coupling; Magnetic anisotropy; Spin transfer torque; ANISOTROPY; FILMS